Physician perceptions about living organ donation in patients with Amyotrophic Lateral Sclerosis - Ansari, S (Clin Neurol Neurosurg, 2017)
OBJECTIVES: Patients with Amyotrophic Lateral Sclerosis (ALS) have expressed desire to become living organ donors but are unable to do so with current organ donation policies. Our objective is to assess ALS patient's interest in organ donation, and perceived concerns of this practice by ALS neurologists. PATIENTS AND METHODS: An electronic survey was administered to ALS neurologists across the United States regarding living organ donation in ALS patients prior to respiratory failure. RESULTS: 52 complete responses were received from 121 invites. 67% (35/52) of neurologists expressed no concerns about living organ donation in ALS patients, and 33% had concerns. The concerns related to respiratory failure, anesthesia exposure and renal dysfunction. With their concerns addressed, 71% of neurologists reported that they would endorse living organ donation. 49% of neurologists reported being asked by a patient for information regarding living organ donation. ALS neurologists felt that 22.8% of ALS patients (median 19%) would be interested in learning more about organ donation, while only 6% of neurologists broach this subject with their patients. CONCLUSION: Our results indicate that 1 in every 4 ALS patients may be interested in exploring options for living organ donation, and this topic is not routinely addressed by ALS clinics. These results indicate an unexplored area of patient interest. To honor a patient's wishes to donate, the transplant community will have to accommodate living organ donation from terminally ill patients, and address neurologist concerns. Such a practice could benefit two groups of patients.